Analisa TTFB Website Pariwisata Karaton Ngayogyakarta Hadiningrat Melalui SpeedVitals Dengan Arsitektur JAMstack - Abiyyu, Zaky (JATISI, 2025)
Tourism websites play a vital role in disseminating information and promoting cultural destinations such as the Karaton Ngayogyakarta Hadiningrat. The server’s initial response speed, or Time to First Byte (TTFB), is an important indicator in evaluating user experience when visiting a website. This study aims to demonstrate improved TTFB performance by implementing a web development architecture known as JAMstack. TTFB testing was conducted using the SpeedVitals platform, measuring four key components that make up the full TTFB metric: DNS, Connect, TLS, and TTFB itself, across various locations worldwide. The results show that websites built with JAMstack architecture consistently achieve faster TTFB, ranging from 54 ms to 228 ms across approximately 32 locations. This stands in contrast to the non-JAMstack approach, which shows inconsistent results ranging from 427 ms to 909 ms. This performance advantage is attributed to the delivery of static content via a Content Delivery Network (CDN) with hundreds of global distribution points. In addition to offering faster access and a more consistent user experience from various global regions, JAMstack also provides reliability, redundancy, and ease of migration. Based on these findings, JAMstack proves to be a superior architectural approach for developing tourism websites that require fast and stable access across regions.